The Enhanced Games: a timely injection for the International Olympic Committee - Ekdahl, David; Krieger, Jörg (Frontiers in Sports and Active Living, 2024)
The Enhanced Games, a privately funded sporting megaevent aspiring to rival the Olympic Games, have garnered significant media attention since its public inception in 2023. This attention has primarily been driven by the Enhanced Games’ embrace of performance-enhancing drugs. Lost in the public fixation on the event’s green-lit drug-use, however, is the fact that the Enhanced Games distance themselves from current Olympic standards in numerous ways beyond drug-policies alone. More precisely, the Enhanced Games promote themselves as a more economically and ecologically sustainable alternative to the Olympics, as well as a megaevent that aims to put athletes and their safety front-and-center. With an eye towards current Olympic standards, we suggest that closer examination of the Enhanced Games offers novel perspectives on the future of the Olympics and global sporting events more broadly.